2022
DOI: 10.3390/molecules27196380
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical and Antioxidant Potentialities in Chilli: Perspectives and Way Forward

Abstract: Worldwide, since ages and nowadays, traditional medicine is well known, owing to its biodiversity, which immensely contributed to the advancement and development of complementary and alternative medicines. There is a wide range of spices, herbs, and trees known for their medicinal uses. Chilli peppers, a vegetable cum spice crop, are bestowed with natural bioactive compounds, flavonoids, capsaicinoids, phytochemicals, phytonutrients, and pharmacologically active compounds with potential health benefits. Such c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 226 publications
0
11
0
1
Order By: Relevance
“…As chili pepper contains high level of vitamin C, E, anthocyanin, and phenolic compounds it showed strong antioxidant activities in vitro, in vivo, and clinical studies [103][104][105][106][107]. From earlier research studies it was demonstrated a positive correlation between phenolic content and antioxidant potential with strong radical scavenging activities in ABTS, DPPH, and FRAP assays [103].…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…As chili pepper contains high level of vitamin C, E, anthocyanin, and phenolic compounds it showed strong antioxidant activities in vitro, in vivo, and clinical studies [103][104][105][106][107]. From earlier research studies it was demonstrated a positive correlation between phenolic content and antioxidant potential with strong radical scavenging activities in ABTS, DPPH, and FRAP assays [103].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…It has been shown that capsaicin could reduce inflammations in different animal models and human trials. Capsacin has been reported to have anti-inflammatory activities by inhibiting the NO, IL-6, and TNF-α in LPS-induced in RAW 264.7 cells [107,108]. Capsaicin reduced the inflammatory responses by inhibiting the pro-inflammatory cytokines such as interleukin 1β (IL-1β) and tumor nuclear factor-kappa (NF-κ) [109].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…[27] When these compounds come into contact with oxidizable substances, they can significantly slow or prevent the oxidation of these substances, even at low concentrations. [28] Puerarin (Figure 1) is derived from the root of the kudzu plant, whose latin name is Pueraria lobata. [29] Puerarin has a wide range of uses such as vasodilation, cardioprotection, neuroprotection, antioxidant, alleviating pain, promoting bone formation, and reducing insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[27] The working principle of antioxidants is to reduce or prevent attacks on cells by neutralizing free radicals. [28] For this reason, as mentioned above, the importance of natural antioxidants has increased a lot and studies on this have gained momentum. [29] Alzheimer's disease, which is one of the diseases caused by ROS, does not have a definite treatment today, only drug treatment is applied to reduce the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation